(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Mishalova O. V. Processing of original sources as an effective method of forming long-lasting knowledge and developing critical thinking skills in university students. The paper deals with didactic possibilities of using individual and instructor-led processing of original sources in teaching human sciences (philosophy, history, religion studies, culture studies). The claim is that processing of original sources is as an effective method of forming long-lasting knowledge and developing critical thinking skills in university students.